A review of the literature on cardiac electrical activity between fibroblasts and myocytes. Issue 1 (January 2016) - Mahoney, Vanessa M.; Mezzano, Valeria; Morley, Gregory E.
Abstract: Myocardial injuries often lead to fibrotic deposition. This review presents evidence supporting the concept that fibroblasts in the heart electrically couple to myocytes.